Ethnographic Exploration of Multinational Corporate Culture and Innovation at Lazada Logistics Bandung - Ganjar Kurniawan Ramdani; Ike Juanita Triwardhani; O Hasbiansyah (INJECT (Interdisciplinary Journal of Communication), 2026)
This study employs an ethnographic communication approach to explore how multinational corporate culture influences innovation at Lazada Logistics Indonesia’s Bandung Regional branch, with a focus on communication practices, organizational culture, and multicultural dynamics. Findings reveal a complex relationship among factors contributing to innovation. Lazada’s multinational culture, characterized by workforce diversity and inclusive communication, fosters creativity and collaboration. Data were collected over two months through participant observation, five in-depth interviews, and fifteen focus group discussions with participants across management, operational, and support staff. The use of multiple languages, primarily Bahasa Indonesia supplemented by English, promotes inclusivity while also presenting challenges such as language barriers. Leadership emerged as a key facilitator, with transformational leadership styles effectively inspiring employees. However, challenges include balancing operational demands with innovation, managing cultural diversity, and addressing communication barriers. These findings contribute to understanding how trusted community-embedded structures mediate the translation of organizational culture into innovative behavior in LMIC-adjacent corporate settings.This study employs an ethnographic communication approach to explore how multinational corporate culture influences innovation at Lazada Logistics Indonesia’s Bandung Regional branch, with a focus on communication practices, organizational culture, and multicultural dynamics. Findings reveal a complex relationship among factors contributing to innovation. Lazada’s multinational culture, characterized by workforce diversity and inclusive communication, fosters creativity and collaboration. Data were collected over two months through participant observation, five in-depth interviews, and fifteen focus group discussions with participants across management, operational, and support staff. The use of multiple languages, primarily Bahasa Indonesia supplemented by English, promotes inclusivity while also presenting challenges such as language barriers. Leadership emerged as a key facilitator, with transformational leadership styles effectively inspiring employees. However, challenges include balancing operational demands with innovation, managing cultural diversity, and addressing communication barriers. These findings contribute to understanding how trusted community-embedded structures mediate the translation of organizational culture into innovative behavior in LMIC-adjacent corporate settings.